VISTA Variables in the Vía Láctea (VVV): Halfway Status and Results - Hempel, Maren (2014)
The VISTA Variables in the Vía Láctea (VVV) survey is one of six near-infrared ESO public surveys, and is now in its fourth year of observing. Although far from being complete, the VVV survey has already delivered many results, some directly connected to the intended science goals (detection of variable stars, microlensing events, new star clusters), others concerning more exotic objects, e.g., novae. Now, at the end of the fourth observing period, and comprising roughly 50% of the proposed observations, the status of the survey, as well some of results based on the VVV data, are presented.